Pengaruh Kualitas Pelayanan dan Kepuasan Nasabah Terhadap Switching Intention pada Nasabah Bank Panin Kota Sungai Penuh Periode Tahun 2016 - Edia Satria (Universitas Batanghari, 2019)
This study aimed to find out 1) what is the influence of service quality to switching intention to Bank Panin customers of Sungai Penuh City? 2) the extent to which the effect of customer satisfaction on switching intention on customer Bank Panin Sungai Penuh City? 3) the extent of the influence of service quality to switching intention either directly or indirectly? 4) the extent to which customer satisfaction satisfaction of customer service to switching intention either directly or indirectly? The population in this research is Bank Panin customer period 2016. hence got sample size 51 customer with accidental sampling, sampling technique. The data analysis tool used is path analysis at alpha level of 0.05. Based on the result of research indicate that service quality has no significant effect to switching intention, customer satisfaction has positive and significant effect to switching intention.